Socket seal surgery techniques in the esthetic zone: a systematic review with meta-analysis and trial sequential analysis of randomized clinical trials - Andrea López-Pacheco; David Soto-Peñaloza; Mayra Gómez; David Peñarrocha-Oltra; Marco Antonio Alarcón (SpringerOpen, 2021)
Abstract Background The socket seal surgery (SSS) technique is a common alternative for the management of the post-extraction sockets that requires a primary closure of the wound to promote proper regeneration and ridge preservation. Objective To learn about the effect of different SSS techniques on alveolar ridge preservation Material and methods Two independent and calibrated reviewers conducted an electronic search in PubMed, Cochrane, and Web of Science for randomized clinical trials (RCT) published up to June 2020. The evaluation of the risk of bias in the included studies was carried out following the Cochrane manual for interventions of systematic reviews, version 5.1.0. A meta-analysis of ridge width changes at − 1, − 3, and − 5 mm cutoff points from bone crest was conducted using a random-effects model. The risk of types I and II errors against accrued data was appraised obtaining the required information size using a trial sequential analysis package (TSA). Results A total of 135 sockets located in the esthetic zone were evaluated with a minimum of a 3-month follow-up after tooth extraction in 6 RCTs. The evaluated SSS techniques were free gingival graft (FGG), collagen matrix (CM), collagen sponge (CS), acellular dermal matrix (ADM), and polytetrafluoroethylene membrane (PTFEm). The FGG in sockets without bone filling showed significant results in preserving both buccal and lingual bone height (− 1.42 mm in the experimental group versus − 0.01 in the control group). The comparison of CM and FGG with bone filling did not show clinical differences in terms of dimensional bone changes. No clinical differences were found in either width or gingival thickness when comparing CM and CS. The meta-analyses of RW changes comparing CM versus FGG showed no significant differences, but a trend for lessening horizontal reduction at − 1, − 3, and − 5 mm in favor of FGG. The TSA showed that accrued data did not reach the required information size, and more evidence is required for clinical significance inferences. Conclusions There are several predictable SSS techniques to improve clinical results in ridge preservation. More clinical studies in the form of clinical trials are required to demonstrate the superiority of one technique over another.